Paternal developmental thyrotoxicosis disrupts neonatal leptin leading to increased adiposity and altered physiology of the melanocortin system - Martinez, Maria Elena; Wu, Zhaofei; Hernandez, Arturo (Frontiers in Endocrinology, 2023)
The genetic code does not fully explain individual variability and inheritance of susceptibility to endocrine conditions, suggesting the contribution of epigenetic factors acting across generations. Here we analyzed the endocrine physiology phenotypes that occur as a result of paternal over exposure to thyroid hormones during development. Compared to controls, adult females with an exposed father (EF females) exhibited significantly elevated body weight and fat mass, but not lean mass, a phenotype that was much milder in EF males. After fasting, both EF females and males exhibited a more pronounced decrease in body weight than controls. EF females also showed markedly elevated serum leptin, increased expression of the leptin gene (Lep) and of mesoderm-specific transcript (Mest) in white adipose tissue but decreased expression of type 2 deiodinase (Dio2) expression. EF females exhibited decreased serum ghrelin, which showed more pronounced post-fasting changes in EF females than in control females. At baseline, the hypothalamus of EF females also revealed significant decreases in the expression of pro-opiomelanocortin (Pomc), agouti-related peptide (Agrp), neuropeptide Y (Npy) and melanocortin receptor 4 (Mc4r). These markers also showed larger changes in response to fasting in EF females than in control females. Concerning the thyroid axis, EF females showed no abnormalities in serum thyroid hormones, but pituitary expression of thyrotropin-releasing hormone receptor 1 (Trhr1) and thyroid gland expression of thyroid-stimulating hormone receptor (Tshr), thyroid peroxidase (Tpo) and iodotyrosine deiodinase (Iyd) were increased at baseline and showed differential regulation after fasting, with no increase in Trhr1 expression and more pronounced reductions in Tshr, Tpo and Iyd. In EF males, these abnormalities were generally milder. In addition, postnatal day 14 (P14) serum leptin was markedly reduced in EF pups. Overall our results show that a paternal excess of thyroid hormone during development modifies the endocrine programming and energy balance in the offspring in a sexually dimorphic manner, with baseline and dynamic range alterations in the leptin-melanocortin system and thyroid gland, and consequences for adiposity phenotypes. We conclude that thyroid hormone overexposure may have important implications for the non-genetic, inherited etiology of endocrine and metabolic pathologies.